Synthesis and Biological Evaluation of Some N‐Arylpyrazoles and Pyrazolo[3, 4‐d]pyridazines as Anti‐Inflammatory Agents. Issue 9 (23rd August 2013) - El‐Sabbagh, Osama I.; Mostafa, Samia; Abdel‐Aziz, Hatem A.; Ibrahim, Hany S.; Elaasser, Mahmoud M.
<x xml:space="preserve">Abstract</x> A series of 3, 4‐bis‐chalcone‐N‐arylpyrazoles 3a–k was prepared from diacetyl pyrazoles 2a–e. The reaction of 2d and 2e with hydrazine hydrate gave pyrazolo[3, 4‐d]pyridazine derivatives 4a–b. Furthermore, the reaction of 2a–e with thiosemicarbazide afforded pyrazolo[3, 4‐d]pyridazine thiocyanate salts 5a–e. The synthesized compounds were subjected to in vivo anti‐inflammatory and ulcerogenic activity measurements, in addition to determination of their in vitro COX selectivity, to give a full profile about their anti‐inflammatory activities. Compounds 3c, 3f, 3i, and 3e showed significant anti‐inflammatory activity among the synthesized compounds. Moreover, docking studies were performed to give an explanation for their anti‐inflammatory activity through COX selectivity.